Graphene quantum dot-mediated atom-layer semiconductor electrocatalyst for hydrogen evolution - Hu, Bingjie (2024)
The hydrogen evolution reaction performance of semiconducting 2H-phase molybdenum disulfide (2H-MoS2) presents a significant hurdle in realizing its full potential applications. Here, we utilize theoretical calculations to predict possible functionalized graphene quantum dots (GQDs), which can enhance HER activity of bulk MoS2. Subsequently, we design a functionalized GQD-induced in-situ bottom-up strategy to fabricate near atom-layer 2H-MoS2 nanosheets mediated with GQDs (ALQD) by modulating the concentration of electron withdrawing/donating functional groups. Experimental results reveal that the introduction of a series of functionalized GQDs during the synthesis of ALQD plays a crucial role. Notably, the higher the concentration and strength of electron-withdrawing functional groups on GQDs, the thinner and more active the resulting ALQD are. Remarkably, the synthesized near atom-layer ALQD-SO3 demonstrate significantly improved HER performance. Our GQD-induced strategy provides a simple and efficient approach for expanding the catalytic application of MoS2. Furthermore, it holds substantial potential for developing nanosheets in other transition-metal dichalcogenide materials.